Three-layer collagen-based vascular graft designed for low-flow peripheral vascular reconstructions - Špaček, Miroslav; Chlup, Hynek; Mitáš, Petr; Veselý, Jan; Lambert, Lukáš; Mlček, Mikuláš; Krajíček, Milan; Lindner, Jaroslav; Grus, Tomáš (Journal of Applied Biomedicine, 2019)
Introduction: The aim of this study was to develop a prototype of an artificial blood vessel which has similar mechanical properties to a human saphenous vein graft and to experimentally verify the function of the prosthesis via ovine carotid bypass implantation. Material and methods: The prototype of an artificial graft prosthesis for low flow was developed and manufactured from a collagenous matrix and reinforcing polyester mesh. We compared the results of both the pressurisation and the mechanical stress evaluation tests of VSM with four types of hybrid vascular graft. The most similar graft (type II) was chosen for the first ovine model implantation. Results: Dominant behavior e.g. mechanical response of VSM graft in plots of circumferential and axial stress during loading is observed in circumferential direction. Average results of used VSM showed area of ideal mechanical response and the properties of artificial blood vessels were fitted into this area. Developed graft remained patent after 161 days of follow up in ovine model. Conclusions: The mechanical properties of the graft were designed and adjusted to be similar to the behaviour of human saphenous veins. This approach showed promising results and enhanced the final performance of the prosthesis.
Keywords: mechanický stres; cévní protézy; složené pryskyřice; chirurgické síťky; Collagen; Stress, Mechanical; Saphenous Vein; kolagen; Blood Vessel Prosthesis Implantation; Blood Vessel Prosthesis; vena saphena; Surgical Mesh; cévy - implantace protéz; Composite Resins